FAKTOR YANG MEMPENGARUHI KUALITAS HIDUP PADA LANJUT USIA - Indah Mulya Destriande; Intan Faridah; Kharisma Oktania; Syahnur Rahman (Fakultas Psikologi Universitas Wijaya Putra, 2021)
Kuality of life is a broad concept that has many influencing factors. This study aims to determine the factors that affect the quality of life of the elderly, the factors found to affect the quality of life of the elderly include family support, peer support, living environment, physical health, psychological health, health services, marital status, economic level. Education, and spiritual. This study used the literature study method, the literature study was conducted in 33 major journals and several other journals as additions.